EXPLORING MUSLIM CONSUMERS' INTENTIONS TOWARD IMPORTED HALAL FOOD: AN INTEGRATION OF TCV AND TPB - Jatnika, Muhammad Dzulfaqori; Friantoro, Dian; Bunda, Cici Aulia Permata; Rahmawati, Yesi (Ekonomi Islam, 2025)
Research aims: To examine the consumption value factors influencing Muslim consumers’ purchase motives for imported halal products in West Java and to analyze the role of attitude, subjective norms, and perceived behavioral control in shaping purchase intention. Design/Methodology/Approach: A quantitative approach was applied through a survey of 273 purposively selected respondents, with data analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Research findings: The results show that attitude and perceived behavioral control significantly affect purchase intention, whereas subjective norms have no meaningful impact. Quality, price, and emotional values strongly influence attitude and, through it, enhance behavioral intention, while conditional values show no significant role. These findings suggest that intrinsic consumption values and positive attitudes are the main drivers of intention, highlighting the limited effect of social and situational factors. Theoretical Contribution/Originality: Integrates the Theory of Consumption Values (TCV) and the Theory of Planned Behavior (TPB) to explain how intrinsic motivations outweigh external pressures in shaping halal consumption behavior. Practitioners/Policy Implications: Practically, policymakers and halal certification bodies should strengthen trust in product quality and authenticity while fostering emotional engagement through branding and communication strategies. Rather than focusing on social influence or temporary promotions, sustainable growth in halal consumption depends on nurturing intrinsic values and favorable consumer attitudes. Research Limitations/Implications: The study is limited to Muslim consumers in West Java; future research could employ longitudinal or mixed methods, compare regions, or explore variables such as religiosity, trust in certification, and digital influence.